Implementation of the Reciprocal Teaching Model in Fiqh Learning to Improve Students' Learning Independence - Mhd. Farizal Fadly; Ali Imran Sinaga; Haidir Haidir (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to analyze the implementation of the Reciprocal Teaching model in fiqh learning and its impact on the learning independence of ninth-grade students at MTs YAPNI Tanjung Morawa. The background of this research is the low learning independence of students due to the dominance of teacher-centered learning methods. The study uses a qualitative approach with a case study type. The research subjects consist of fiqh teachers and ninth-grade students selected purposively. Data collection techniques include observation, in-depth interviews, and documentation, while data analysis uses the Miles and Huberman interactive model through data reduction, data presentation, and drawing conclusions. The research results show that the implementation of Reciprocal Teaching has been carried out systematically through activities of summarizing, questioning, clarifying, and predicting, supported by learning tools such as lesson plans and student worksheets. This model has been proven to increase students' activeness, engagement, and social interaction, thereby promoting the development of learning independence. However, its implementation still faces challenges such as limited time, uneven student participation, and low self-confidence in some students. Thus, Reciprocal Teaching is an effective learning model for enhancing students' learning independence, but it requires strengthening in classroom management and teacher guidance to achieve more optimal results.